2016
DOI: 10.1016/j.apcatb.2015.10.021
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and photocatalytic performance of yttrium-doped CeO2 with a porous broom-like hierarchical structure

Abstract: In this study, yttrium-doped CeO2 with a broom-like porous hierarchical structure was successfully prepared by a simple template-free hydrothermal method with cerium nitrate hexahydrate and yttrium nitrate hexahydrate as original materials. Through systematic experiments, the different effects of doping concentrations on characteristics of the ceria were examined in detail and the optimal doping ratio was determined simultaneously. The morphology and element distribution of the as-prepared samples were charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 39 publications
(48 reference statements)
2
20
0
Order By: Relevance
“…b). It is found that there were three sets of lattice fringes with interplanar spacings of 0.319 nm, 0.273 nm and 0.314 nm, corresponding to the (131) and (200) planes of orthorhombic Bi 2 WO 6 and the (111) plane of cubic fluorite‐type CeO 2 , respectively, which was consistent with the results of XRD. It evidently revealed that the compounds of CeO 2 and Bi 2 WO 6 were formed in the microspheres.…”
Section: Resultssupporting
confidence: 86%
“…b). It is found that there were three sets of lattice fringes with interplanar spacings of 0.319 nm, 0.273 nm and 0.314 nm, corresponding to the (131) and (200) planes of orthorhombic Bi 2 WO 6 and the (111) plane of cubic fluorite‐type CeO 2 , respectively, which was consistent with the results of XRD. It evidently revealed that the compounds of CeO 2 and Bi 2 WO 6 were formed in the microspheres.…”
Section: Resultssupporting
confidence: 86%
“…The shift at ~460 cm -1 can be assigned to F2g vibration of the fluorite-type structure and it can be considered as the symmetric stretching mode of oxygen atoms around cerium ions, and the molecule retains its tetrahedral symmetry throughout. Based on the results of previous studies and our own studies [43][44][45], a weak and less prominent band near ~600…”
Section: Structure Characterizationmentioning
confidence: 90%
“…When the number of oxygen vacancies is larger, the oxygen ion mobility becomes higher. Transportation mobility of lattice oxygen ions is beneficial for the separation of photogenerated electrons and holes [43][44][45]. In another word, the recombination of photogenerated electrons and holes is restricted at a higher oxygen vacancy.…”
Section: Photocatalytic Activity For Acetaldehyde Decompositionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 a shows the Ce3 d XPS spectrum and its fitted deconvolutions of the as‐synthesised nanoparticles. The peaks located at 881.85, 888.43, 897.58, 900.03, 907.53, and 916.99 eV are attributed to Ce 4+ ions, while those at 883.99 and 903.10 eV are the characteristic peaks of Ce 3+ [7]. This result implies that both Ce 4+ and Ce 3+ ions coexist, and there are surface Ce 4+ /Ce 3+ pairs in the CeO 2 nanocolumns.…”
Section: Resultsmentioning
confidence: 99%